Respon Pertumbuhan Pada Kacang Panjang (Vigna sinensis L.) Terhadap Pemberian Pupuk Organik Cair (POC) Nasa dan Pupuk NPK - Kasfar, Fidel; Khairani, Siti; Fahri, Romi (Agroprimatech, 2024)
Long bean plants are a horticultural commodity that has the potential to be developed because they have quite high nutritional and economic value. In order for long beans to grow optimally, organic and inorganic fertilizers can be applied. This research aims to determine the effect of providing organic and inorganic fertilizers and the correct dosage on the growth of long beans. This research used a factorial Randomized Block Design (RBD) with 2 factors and 3 replications. The first factor is the application of Nasa liquid organic fertilizer (LOF) at 4 levels, namely: C0 (0 ml/liter of water/control), C1 (2 ml/liter of water), C2 (4 ml/liter of water) and C3 (6 ml /liter of water). The second factor is the application of NPK fertilizer at 4 levels, namely: N0 (control), N1 (dose 200 kg/ha or 20 g/plot), N2 (dose 300 kg/ha or 30 g/plot), N3 (dose 400 kg /ha or 40 g/plot). The research results showed that Nasa LOF application and NPK fertilizer had a significant effect on plant height at 15 and 30 days after planting (DAP), number of branches at 15 and 30 DAP and flowering age.